Hak-hak Asasi Manusia dalam Islam: Analisis pada Konteks Jar?mah - A'isyah, Siti; Roihanah, Roihanah (Fakultas Syariah - IAI Al-Qolam Malang, 2018)
Islamic penal law is contextual in relation to the concept of rights in Islam because in the punishments of the crimes that are contained in the Koran, rights become very considerable point. There are three types of rights in Islam; creature rights (individual rights), God's rights (public rights) and the combination of both (combined rights of creatures and rights of God). In the Islamic penal law, when the right is violated, the victim can forgive the perpetrator, while the violation of the right of Allah, the punishment cannot be offered because it injures the public's rights. As for the rights, which are a combination of both, victims can forgive the perpetrators, but cannot abolish the penalty for crimes against public rights. The concept of rights in Islam can be an entry point for the contextualization of Islamic criminal law. The form of punishment does not have to be rigid as written in the sacred texts, but can be adaptive to the contexts. Thus, maq?shid al-syar?'ah can still be achieved, and Islamic law can be sh?lih li kull zam?n wa mak?n. Keywords: jar?mah, rights, Islam